Sublethal effects of waterborne copper and copper nanoparticles on the freshwater Neotropical teleost Prochilodus lineatus: a comparative approach - Tesser, Maria Eduarda; Paula, Angélica Alves de; Risso, Wagner Ezequiel; Monteiro, Renata Aparecida; Pereira, Anderson do Espirito Santo; Fraceto, Leonardo Fernandes; Martinez, Claudia Bueno dos Reis (Elsevier, 2020)
Copper nanoparticles can contaminate the aquatic environment, but their effects on fish and how they may differ from copper salts is not understood. Thus, in this work we compare the sublethal effects of copper nanoparticles (nCu) and copper chloride (Cu) on the freshwater teleost Prochilodus lineatus, known for its sensitivity to copper. Juveniles (n = 8/group) were exposed to 20 μg L−1 of copper as CuCl2 (Cu), 40 μg L−1 of copper nanoparticles (nCu), or only water (control), for 96 h. These concentrations were chosen to achieve similar dissolved copper concentration in both treatments (Cu: 10.29 ± 0.94 μg L−1; nCu: 12.16 ± 1.77 μg L−1). After the exposure, the following biological parameters were evaluated: copper accumulation in the gills, liver, gastrointestinal tract, kidney, and muscle; hematocrit (Ht) and hemoglobin content (Hb); branchial activity of Na+-K+-ATPase (NaKATP), H+-ATPase (HATP), Ca2+-ATPase (CaATP), and carbonic anhydrase (CA); glutathione content (GSH) and lipid peroxidation (LPO) in the liver; acetylcholinesterase activity (AChE) in the brain and muscle; and histopathology of the gills and liver. The gills of Cu-exposed fish were adversely affected, with increased copper content, inhibition of H+-ATPase and Ca2+-ATPase, and histological damage, including proliferation of mitochondria rich cells and/or mucous cells. In addition, LPO levels increased in the liver of Cu-exposed fish, indicating the occurrence of oxidative stress. Exposure to nCu promoted a decrease in Ht and Hb, indicating anemia, and an increase in branchial Na+-K+-ATPase and H+-ATPase activities, which can be an adaptive response to metabolic acidosis. Within the chosen biomarkers and the conditions tested, copper nanoparticles were less toxic than copper. However, the effects promoted by the nanoparticles were different from those promoted by copper. These results emphasize the need for a better understanding of copper nanoparticles toxicity in order to establish safe concentrations and avoid environment impacts.
Keywords: Biomarkers; Nanotoxicology; Osmoregulation; Hematology; Fish; Oxidative stress